Management of Gunshot-Induced Mandibular Fracture in a Young Patient Using External Fixation: A Case Report - Lima, Diego Learth; Vidal, Iago Barbosa; Menezes Junior, José Maria Sampaio; Silva, Kariny Oliveira; Cavalcante, Nayara Kelly Silva de Oliveira; Gondim, Ricardo Franklin; Pereira, Rildenson Moura; Bezerra, Ariel Valente (Brazilian Journal of Case Reports, 2024)
The management of gunshot wounds to the face represents a significantly complex challenge due to the need for meticulous surgical interventions. This study aims to report the efficacy of external fixators in treating comminuted mandibular fractures caused by gunshot trauma in a 16-year-old patient. The patient presented to an Oral and Maxillofacial Surgery and Traumatology service with edema, malocclusion, mandibular mobility, spontaneous pain, oral mucosal laceration, paresthesia in the mandibular region, and multiple entry and exit gunshot wounds on the face. Facial computed tomography revealed a frontal sinus fracture, comminuted mandibular body fracture, left zygomatic arch fracture, and right zygoma fracture, in addition to fragments consistent with firearm projectiles adjacent to the right and left mandible, glabella region, and soft tissues on the left side of the face. Given the patient’s clinical complaints, the proposed treatment involved surgical removal of the projectiles under general anesthesia and the use of an external fixator for mandibular fracture stabilization. The patient progressed without complications or clinical complaints, with follow-up over six months showing bone consolidation, satisfactory occlusion, and no clinical or imaging signs of infection. It is concluded that the use of external fixators in comminuted mandibular fractures is an effective approach, ensuring good recovery, preserving aesthetic and functional outcomes, and minimizing the risk of infections and other complications.